2014
DOI: 10.1519/jsc.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest Reliability and Sensitivity of the Concept2 Dyno Dynamometer

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and not-for-profit activities provided that• the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…29 While this effect is quite small, with increases in performance ranging between 0.5 to 1.9% between an initial and subsequent sessions, there is some consensus that a familiarization session is necessary, particularly in athletes but also in non-athletes, to ensure the stability of force outcomes. [30][31][32][33][34] While this is, to our knowledge, the first investigation into the effects of a familiarization session on dynamometric measures of female PFM properties, previous authors have suggested that a familiarization effect may exist. Using a Peritron™ Perineometer (Queensland, Australia), Jacamo et al 13 observed that a group of women who received a single education session about genital anatomy and PFM function generated higher vaginal pressure (15.2 mmHg) during maximal effort voluntary PFM contraction after compared to before (12.6 mmHg) the session.…”
Section: The Impact Of a Familiarization Session On Dynamometric Outcmentioning
confidence: 77%
See 1 more Smart Citation
“…29 While this effect is quite small, with increases in performance ranging between 0.5 to 1.9% between an initial and subsequent sessions, there is some consensus that a familiarization session is necessary, particularly in athletes but also in non-athletes, to ensure the stability of force outcomes. [30][31][32][33][34] While this is, to our knowledge, the first investigation into the effects of a familiarization session on dynamometric measures of female PFM properties, previous authors have suggested that a familiarization effect may exist. Using a Peritron™ Perineometer (Queensland, Australia), Jacamo et al 13 observed that a group of women who received a single education session about genital anatomy and PFM function generated higher vaginal pressure (15.2 mmHg) during maximal effort voluntary PFM contraction after compared to before (12.6 mmHg) the session.…”
Section: The Impact Of a Familiarization Session On Dynamometric Outcmentioning
confidence: 77%
“…We expected that a familiarization session would be necessary in order to minimize the impact of motor learning on maximal PFM activation, since a learning effect has been observed for other skeletal muscle groups including the quadriceps, the hamstrings and the biceps brachii . While this effect is quite small, with increases in performance ranging between 0.5 to 1.9% between an initial and subsequent sessions, there is some consensus that a familiarization session is necessary, particularly in athletes but also in non‐athletes, to ensure the stability of force outcomes …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is crucial in determining the efficacy of human body movements and guaranteeing joint stability and posture maintenance [ 1 ]. Muscle strength has been the object of many studies in the sports field, in which the relationship between muscle strength, training, level of competition, and performance has been explored [ 2 , 3 , 4 ]. Moreover, strength training is increasingly being used in managing various conditions such as sarcopenia [ 5 ] or osteoarthritis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial in determining the efficacy of human body movements and guaranteeing joint stability and posture maintenance [7]. Muscle strength has been the object of many studies in which the relationship between muscle strength, training, level of competition, and performance has been explored [8][9][10]. The role of muscle strength deficits as possible risk factors for lower limb injuries represents a debated topic.…”
Section: Introductionmentioning
confidence: 99%